ANALISA PERBANDINGAN PENGGUNAAN KATA KETERANGAN DERAJAT BAHASA MANDARIN DAN BAHASA INDONESIA - Putri Mustika Susilo (Business Economic, Communication, and Social Sciences (BECOSS) Journal, 2019)
Both modern Chinese and Bahasa have adverbs in common. In adverb, adverb of degree plays an important role in grammar as well as to express level of degree itself. Although there are a few of them, only around a dozen are being used frequently. Main usage of Chinese degree adverb is to qualify psychological verb, adjective and also noun. Main usage of Bahasa degree adverb is to adverbial. The position of Bahasa degree adverb is so ﬂexible that can be used in before and after subject, or in the last sentence. There are similarities and also diﬀerences in the usage from both Chinese and Bahasa. Thus, in the process of learning the adverb of degree in Chinese, foreign student or in this case Indonesian students fnd it a little hard to understand. Indonesian students who learn Chinese usually make bias or error during the learning adverb of degree. These bias and error would inﬂuence the accuracy of expression used directly. The author will analyze degree adverb’s the similarities and diﬀerences using literature collection method in this research. At the same time, for Indonesian students learning degree adverb aspect put forward more suitable teaching and studying suggestions. Based on that, the author will only focus on commonly used adverb of degree such as “very, highly, extremely, to what extent, rather, too, fully, most, more, and a little”, to minimalize the bias that the students make. There are explanations in every example for using Chinese and Bahasa degree adverb. The author hopes this research can help Indonesian students to learn Chinese adverbs of degree further